2018
DOI: 10.1177/1934578x1801300713
|View full text |Cite
|
Sign up to set email alerts
|

A New Flavanone from Seeds of Psoralea corylifolia with α-Glucosidase Inhibitory Activity

Abstract: A new flavanone (2S)-7,4'-hydroxyl-6-(2'',3''-epoxy-3''-methylbutyl)flavanone (1), together with five known compounds (2-6) were isolated from EtOAcsoluble extract of seeds of Psoralea corylifolia. Their structures were elucidated on the basis of spectroscopic and physico-chemical analyses. All compounds were evaluated for in vitro inhibitory activity against α-glucosidase. Among them, new compound 1 was found to exhibit inhibitory activity on α-glucosidase with IC 50 value of 29.2 µM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Finally, an exhaustive analysis of NMR data, considering the quaternary and oxygenated carbons, and comparison with literature data (Ariyasena et al, 2004, et al, 2002) suggested that the linkage between the flavanone/flavone units is made up of ether between I-C-3´and II-C-4´´´, which was confirmed by heteronuclear multiple bond connectivity experiment (HMBC) (Figure 2). A comparison with the literature on flavanones related to the values of the diaxial coupling between H-2 and H-3 (J =12.8 Hz) suggested that the configuration of C-2 is S, with an optical rotation of (-19.5 o ) (Liu et al, 2018, Kang et al, 2000. A search in the literature data of the characterized compound showed, first that the methylenedioxy group is not very common in reported biflavonoids, and that the molecular weight and formula assigned to compound 1 did not lead to a known structure.…”
Section: Resultsmentioning
confidence: 84%
“…Finally, an exhaustive analysis of NMR data, considering the quaternary and oxygenated carbons, and comparison with literature data (Ariyasena et al, 2004, et al, 2002) suggested that the linkage between the flavanone/flavone units is made up of ether between I-C-3´and II-C-4´´´, which was confirmed by heteronuclear multiple bond connectivity experiment (HMBC) (Figure 2). A comparison with the literature on flavanones related to the values of the diaxial coupling between H-2 and H-3 (J =12.8 Hz) suggested that the configuration of C-2 is S, with an optical rotation of (-19.5 o ) (Liu et al, 2018, Kang et al, 2000. A search in the literature data of the characterized compound showed, first that the methylenedioxy group is not very common in reported biflavonoids, and that the molecular weight and formula assigned to compound 1 did not lead to a known structure.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, the comparison of NMR data between 1 and (2 S )−7,4'-hydroxyl-6-(2'',3''-epoxy-3''-methylbutyl) flavanone further confirmed the structure of 1 . 14 Because of the small amount of 1 available, the absolute configuration of C-2'' was not determined. Thus, the structure of compound 1 was determined as 6-(2'',3''-epoxy-3''-methylbutyl)-resokaempferol.…”
Section: Resultsmentioning
confidence: 99%